Paparan Asap Rokok pada Balita Stunting di Kota Banda Aceh - Nailussa’dah, Nailussa’dah; Diba, Farah; Maulina, Maulina (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2024)
Background. Stunting among toddlers is still a serious problem in Indonesia. One of indirect causes is the exposure to cigarette smoke. The purpose of this study is to determine the smoke exposure in toddlers from its duration of exposure, source of exposure and location of cigarette smoke exposure in stunted toddlers in Banda Aceh City. Methods. This study uses a descriptive design and a cross sectional study approach. The population of this study is 233 family with stunting toddlers in one of the Banda Aceh City Districts and the sample of this study amounted to 70 respondents using purposive sampling technique. This research used a questionnaire and the data is analyzed with SPSS. Results. The results showed that 57.1% of stunted toddlers were exposed to cigarette smoke with a duration equal to or more than 3 hours / day. The highest source of cigarette smoke exposure in stunted toddlers is from their father as many as 87.1%. The type of cigarette often used by the source of cigarette smoke exposure in this study is filter cigarettes as many as 97%. The number of cigarettes often consumed by the source of cigarette smoke exposure at home in stunted toddlers is more than 10 cigarettes per day as many as 48.6%. As much as 64.3% toddlers who became passive smokers or third smokers. The location of cigarette smoke exposure is mostly at home and public places, namely 90.0% respondents. Conclusion. This research is showing the evidence that the cigarete smoking exposure is still happened in the house of stunted toddlers where the source of exposure is from the father or family members and the duration of exposure is mostly more than 3 hours a day where it is become the indirect cause of stunting case.